Coal-derived graphene quantum dots with a Mn2+/Mn7+ nanosensor for selective detection of glutathione by a fluorescence switch-off–on assay. (1st April 2022) - Kundu, Aayushi; Maity, Banibrata; Basu, Soumen
Abstract : Coal derived GQDs-Mn 2+ /Mn 7+ nanosensor for the sensitive detection of GSH. Abstract : Coal is an abundant, low-cost, and high carbon content energy source on the planet. Herein, water-soluble graphene quantum dots (GQDs) were prepared from Indian anthracite and bituminous coals labelled as A-GQDs and B-GQDs, respectively, by a facile one-step wet chemical route. The size of the B-GQDs (7.38 ± 0.13 nm) was smaller than that of the A-GQDs (10.25 ± 0.19 nm), which was analysed from TEM. The effects of pH, temperature and irradiation time on the fluorescence of the GQDs have been studied, which confirmed the stability of the GQDs. Moreover, both of the synthesized GQDs exhibited tunable photoluminescence (PL) properties and excitation wavelength dependency. The developed GQDs were highly selective and sensitive for Mn n + (2+, 7+) ions. However, the as-prepared GQDs showed significant changes in both the steady state absorption and fluorescence intensity, but remained unaltered in the excited state lifetime values in the presence of different Mn n + quenchers, which validated the static quenching mechanism between the GQDs@Mn n + nanoprobes. The prepared nanosensor showed high sensitivity for GSH sensing with a good detection limit of 27 μM for B-GQD@Mn 7+ . Exhibiting low-cost productivity and intriguing photoluminescence properties, the current study reveals new potential for sustainable synthesis of GQDs with novel ascribed attributes.